Detection of Japanese Encephalitis by Metagenomic Next-Generation Sequencing of Cerebrospinal Fluid: A Case Report and Literature Review - Li, Xin; Li, Jing; Wu, Guode; Wang, Manxia; Jing, Zhang (Frontiers in Cellular Neuroscience, 2022)
Japanese encephalitis (JE) is an acute viral central nervous system disease, although less than 1% of patients infected with Japanese encephalitis virus (JEV) result in JE, which has an extremely poor prognosis. The Routine detection methods for JEV are time-consuming or limited by hospital conditions, therefore, need the quicker and sensitive techniques to detect JEV. Here, we reported a 14-year-old female who was admitted to our hospital with a severe fever, progressively headache and unconsciousness. Based on the clinical presentation, Preliminary diagnosis on admission indicated central nervous system infection of suspected viral meningoencephalitis or autoimmune encephalitis. The patient's symptoms were unrelieved after being treated with empiric antiviral therapy. Magnetic resonance imaging (MRI) showed that the lesions were located in the bilateral thalamus, head of caudate nucleus, and right lenticular nucleus, so we had to consider the possibility of Flaviviruses infection. We sent the cerebrospinal fluid (CSF) for metagenomic next-generation sequencing (mNGS) immediately, subsequent result suggested the infection caused by JEV. Two days later the results of the serum agglutination test confirmed that virus immunoglobulin M antibody positive. After a week treatment with intravenous immunoglobulin (IVIG), meanwhile, the lumbar puncture was used to check the pressure and various indicators of the CSF again to evaluate the treatment effect, An decrease in the number of WBC indicates, protein and unique RNA reads that the previous experimental treatment was effective, accompany by temperature and consciousness of the patient was normalized. Two weeks after admission, the patient was transferred to the rehabilitation hospital, MR showed the lesions had disappeared completely after 2 months of follow-up. We believed that mNGS may be an effective method for rapid identification of JE.